KARAKTERISTIK OSEANOGRAFI DI PERAIRAN PROBOLINGGO SEBAGAI DAERAH POTENSIAL PENANGKAPAN IKANTEMBANG(Sardinella fimbriata) - Ully Wulandari; Indra Wirawan; Maria Agustini (Samakia : Jurnal Ilmu Perikanan, 2018)
This research was conducted in October-December 2017 in Probolinggo to determining the potential areas of fishing ground of Sardinella fimbriata by looking at the characteristics of Oceanography in Probolinggo. Research done by survey method to collect primary and secondary data. The data analysis done in a spatial image of MODIS and presented as a oceanographic parameters maps. The results of the analysis showed the waters of Probolinggo oceanographic characteristics are: a) sea surface temperature ranges from 31.3-28.2° C, b) pH 8 ppm, c) salinity between 23%-31%, d) chlorophyll-a 0-4 that shows the chlorophyll-a is high, and e) content of dissolved oxygen (DO) 10 mg/mm3 which indicates that it has a good oxygen for marine life. From the results obtained, the area has finally reached of waters with oceanographic characteristics of the area as a potential fishing ground for Sardinella fimbriata. The potential area of Sardinella fimbriata fishing ground is at madura Strait and waters north of Probolinggo.